The Implementation Of Warm Compresses Made From Lemongrass Leaf Decoction (Cymbopogon Citratus) To Reduce Chronic Pain In Gout Arthritis Patients Through The Application Of Jean Watson's Theory In The Working Area Of Simpang Nangka Health Center In 2025 - Siagian, Ahyu Ismail; Sulastri, Sulastri (Utami Publisher, 2026)
Gout arthritis is a disease characterized by recurrent pain caused by the accumulation of monosodium urate crystals in the joints as a result of high levels of uric acid in the blood. One of these conceptual models is that of Jean Watson. The purpose of this study is for the writer to understand and apply the use warm compresses made from lemongrass (Cymbopogon citratus) to reduce chronic pain in gout arthritis patients through the application of Jean Watson's theory in the working area of Simpang Nangka Health Center. The research method used in this study was a case study, which was used to explore the application of warm compresses made from lemongrass leaf (Cymbopogon Citratus) to reduce chronic pain in gout arthritis patients through the application of Jean Watson's theory in the working area of Simpang Nangka Health Center. The results of the study on client 1 and client 2 showed that in Case 1 and Case 2, the problem of gout arthritis could be resolved, so it was concluded that the application of warm compresses made from lemongrass leaf (Cymbopogon citratus) could reduce pain in patients with gout arthritis. It is hoped that health centers will integrate warm compress therapy using lemongrass leaf decoction as an alternative non-pharmacological therapy for patients with gout arthritis pain.